Amalan kawalan perancangan pihak berkuasa tempatan di Semenanjung Malaysia : tumpuan kepada aspek alam sekitar - Johar, Foziah (2003)
The Malaysia Government's strategy for promoting sustainable development identifies an important role for the town and country planning system. The system is to be a key instrument in delivering land use and development objectives that are compatible with the aims of sustainable development. The recent amendment to the planning legislation indicates the concern for better environmental management both at development plan level and development control. For development control purposes, the local planning authority is empowered to grant planning permissions subject to conditions related to resource conservation and measures which enhance environmental quality of the development. This research aims to assess how far the local planning authority (LPA) provides the framework to guide planning control that can sustain the quality of environment; the considerations that are taken into account in evaluating planning applications and to what extent planning conditions used to achieve planning objectives in protecting the environment and sustainable deve!opment. Content analysis is carried out on 24 local plans used by the respective LPAs to assess the scope of local plan generally and in particular, the strength of environmental coverage of the plans. Content analysis is also carried out on 100 sample files of planning application including the respective development proposal reports to assess planning considerations and the planning conditions particularly on environmental related matters. The perceptions on planning control and environmental aspects of 42 officers involved in planning control from the respective LPAs are obtained using semi-structured questionnaires. The study found that 63% local plans outlined the objectives/strategies related to environmental aspects which emphasised on pollution control of airlwaterlnoise and solid waste management. The majority of proposals on polIution prevention are general in nature without reference to specific sites and method of implementation. 26% planning permission used local plans only to determine the planning decision while the rest refered to various other sources. 85% planning permission referred to local plans to determine the land use. This is much higher compared to 25% planning permission which applied the guidelines to improve environment quality provided by the local plans. The majority of planning conditions emphasised on development form and arrangement, the provision of facilities and infrastructures compared to measures on environmental improvement. The pattern of conditions levied is consistent with the performance of the development proposal reports which lack measures on conserving natural resources. This finding is also consistent with the perception of the majority of respondents who gave priorities to economic and social factors compared to environmental aspects in evaluating planning proposals. The findings of the research indicate the need to improve policies and the implementation of development control towards enhancement of environmental quality in line with the requirement of sustainable development. The main strategy that has been identified is to enhance environmental components at policy formulation and make extensive use of planning conditions towards sustainable land use management through increased awareness among the LPAs